Image Characteristics of the Regions of Kazakhstan (based on the results of a sociological research) - Yessimova, A.B.; Valitova, Z.Kh. (KSU publ., 2020)
The article analyzes the image characteristics of the regions of Kazakhstan formed in the minds of Kazakhstan citizens. Based on the data obtained through expert interviews and questionnaires, the authors found that the economic component prevails in people's ideas about the image. In addition, the main image characteristics of regions in people's perceptions are identical to those of administrative regions of the country. In most cases, a region is synonymous with a province. In particular, the main representatives of the region are cities or regional centers, the image of which extends to the image of the entire region. Cities of regional significance often retain the image characteristics of the industrial Soviet past.
Keywords: Kazakhstan; region; image; social representations; perception of territories; associations